PEREMPUAN TERPANDANG DALAM FILM INDONESIA - Nurmalita Natia Dewi; Sumekar Tanjung (Metacommunication: Journal of Communication Studies, 2020)
This research originated from a phenomenon of women in the mass media which initially served as a satisfaction for the audience with their body shape, but now has begun to fade. Women in the media are the subject and are not underestimated especially in the film media. So as to make the female figure in the film the main character in the storyline which is constructed through the existing reality. And the woman's figure seemed authoritative and classified as a honorable woman who could have a big influence on the people. That way the phenomenon attracted the attention of researchers, because researchers wanted to know how the identity of the honorable women in the film Marlina Si Pembunuh Dalam Empat Babak, 3 Srikandi and Jilbab Traveler: Love Sparks In Korea. With Roland Barthes's semiotic method that reveals the meaning of verbal and non verbal signs with two stages, namely denotations and connotations and associated with myths that develop in society. Then analyzed based on critical views found the identity of respectable women in Indonesian films. The results showed that the identity of a woman in the three films included in the category of social identity. Where the identity is formed due to the influence of interaction in the family and community.